ABA-responsive transcription factor bZIP1 is involved in modulating biosynthesis of phenolic acids and tanshinones in Salvia miltiorrhiza. (26th June 2020) - Deng, Changping; Shi, Min; Fu, Rong; Zhang, Yi; Wang, Qiang; Zhou, Yang; Wang, Yao; Ma, Xingyuan; Kai, Guoyin
Abstract: Phenolic acids and tanshinones are major bioactive ingredients in Salvia miltiorrhiza, which possess pharmacological activities with great market demand. However, transcriptional regulation of phenolic acid and tanshinone biosynthesis remains poorly understood. Here, a basic leucine zipper transcription factor (TF) named SmbZIP1 was screened from the abscisic acid (ABA)-induced transcriptome library. Overexpression of SmbZIP1 positively promoted phenolic acid biosynthesis by enhancing expression of biosynthetic genes such as cinnamate-4-hydroxylase ( C4H1 ). Furthermore, biochemical experiments revealed that SmbZIP1 bound the G-Box-like1 element in the promoter of the C4H1 gene. Meanwhile, SmbZIP1 inhibited accumulation of tanshinones mainly by suppressing the expression of biosynthetic genes including geranylgeranyl diphosphate synthase ( GGPPS ) which was confirmed as a target gene by in vitro and in vivo experiments. In contrast, the phenolic acid content was reduced and tanshinone was enhanced in CRISPR/Cas9 [clustered regularly interspaced palindromic repeats (CRISPR)/CRISPR-associated protein 9]-mediated knockout lines. In addition, the previously reported positive regulator of tanshinone biosynthesis, SmERF1L1, was found to be inhibited in SmbZIP1 overexpression lines indicated by RNA sequencing, and was proven to be the target of SmbZIP1. In summary, this work uncovers a novel regulator and deepens our understanding of the transcriptional and regulatory mechanisms of phenolic acid and tanshinone biosynthesis, and also sheds new light on metabolic engineering in S. miltiorrhiza. Abstract : ABA-responsive transcription factor SmbZIP1 promotes phenolic acid biosynthesis by up-regulating expression of the biosynthetic gene C4H1 but inhibits tanshinone accumulation by repressing the biosynthetic gene GGPPS and the positive regulator SmERF1L1 .